Nīla bidroha o Bāṅālī samāja - Sen Gupta, Promode (Ryāḍikyāla Buka Klāba, 1978)
History of indigo plantation in Bengali and the impact of the 1859-60 Indigo movement on socioeconomic conditions of Bengal; Marxist viewpoint.